Role of Shape and Kinematics in the Hydrodynamics of a Fish-like Oscillating Hydrofoil - Siddharth Gupta; Atul Sharma; Amit Agrawal; Mark C. Thompson; Kerry Hourigan (Journal of Marine Science and Engineering, 2023)
In the present two-dimensional numerical study, we investigate the roles of geometrical parameters of a hydrofoil (shape/curvature of the leading and trailing edges and thickness) and kinematic parameters (phase difference between heave and pitch (ϕ)) on the propulsive performance of different-shaped hydrofoils oscillating at maximum angles of attack up to αmax=30∘. The study was carried out at a fixed non-dimensional maximum heave to chord ratio h∘/C=0.75, Strouhal number St=0.25, and Reynolds number Re=5000. Our findings reveal that hydrofoil performance and stability improve with leading and trailing edge curvatures but decline as thickness increases. By analyzing the near-wake structure, we establish that even minimal flow separation increases power consumption while moderate flow separation enhances thrust. Over the range of different-shaped hydrofoils at different αmax and ϕ, maximum propulsion efficiency occurs for those parameters for which there is a small degree of flow separation but with no roll-up of a separating vortex. In comparison, maximum thrust generation occurs when there is a moderately strong flow separation but without induction of a significant amount of fluid around the trailing edge. These insights offer valuable knowledge for understanding fish propulsion efficiency and have applications in designing autonomous underwater vehicles (AUVs) and micro-air vehicles (MAVs).